PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TUKANGROTI.COM DI BEKASI - Yuliantari, Kartika; Wiwin, Wiwin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
The reasect brand image on Baker Old affects consumers to decide to buy products and can realize the level of sales and progress of the company. The issue to be addressed is whether Baker Old's brand image affects consumer purchasing decisions. The purpose of this study is to determine whether or not there is a brand image of consumer purchasing decisions TukangRoti.com in Bekasi. The method used is quantitative method, collecting the required data through observation, documentation and questionnaire. For the concept of calculation there are validity test, reliability test, population, sample, likert scale, correlation coefficient, determination and regression equation. Testing the indicator or questionnaire of the calculation using SPSS 21. Population in this study are loyal customers Bogor branch. Based on the calculation of regression equation obtained the equation Y = 16,582 + 0,606 X can be interpreted that brand image is constant or 0 value (zero) hence decision of purchase equal to 16,582. The regression coefficient of 0.606 states that every 1 time addition to the brand image will increase the purchase decision by 0.606%.